Kooky campout - Farber, Erica (Richard Scarry's great big schoolhouse readers., 2015)
"Huckle and his friends are going camping. They have tents, fishing poles, sleeping bags, and snacks. They roast marshmallows and someone tells a kooky, spooky ghost story. Will they sleep in their tents all night long?"--Page 4 of cover.